SEBARAN TINGKAT KETAHANAN MASYARAKAT TERHADAP BENCANA BANJIR LAHAR HUJAN SUNGAI CODE - , BULAN NIRWANA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lava flood rain disaster is inherently difficult to predict, although the symptoms and causes can be studied scientifically. Residents who live along the Kali Code have high risk towardlava flood rain. But it does not belittle people's desire to stay in the Code riverbank area. The disaster risk can be reduced by strengthening the community for disaster. This research was conducted in the village of Jogoyudan to determine how the distribution of RW resistance level against floods and rains lava factors affecting the distribution. The location was chosen because Kampung Jogoyudan area had the worst damage by rains lava floods in urban areas compared to Kampung gemblakan. The method used in this study is deductive-inductive qualitative. The framework of analysis used is the Climate and Disaster Resilience Initiative (CDRI). The analysis technique used is the analysis of qualitative, quantitative, and spatial CDRI. From the research conducted, obtained by the finding that components that most affect the distribution of the level of community resilience is a social component, especially in the field of knowledge. In addition, factors that influence the distribution of the level of community resilience in Kampung Jogoyudan are building construction, proximity to roads and mutual help.